COMPARATIVE EDITORIAL ANALYSIS OF PAKISTAN-INDIA RELATIONS WITH REFERENCE TO KASHMIR ISSUE DURING PMLN AND PTI REGIMES IN PAKISTANI PRESS : Pak India Relations - Rizwan, Asim; Dr. Muhammad Yousaf (Journal of Peace, Development and Communication, 2024)
COMPARATIVE EDITORIAL ANALYSIS OF PAKISTAN-INDIA RELATIONSWITHREFERENCETOKASHMIRISSUE DURING PMLN AND PTI REGIMES IN PAKISTANI PRESS ASIM RIZWAN TALIB, PhD Mass Communication Scholar University of Gujrat, Gujrat. Dr. M.Yousaf, Asst Professor University of Gujrat, Gujrat. Abstract Thestudytitled "Comparative editorialanalysisof Pakistan-Indiarelationswithreferenceto Kashmirissueduring PML N and PTI regimesin Pakistani pressaimedatanalyzingtheeditorialcoverageofPakistanileading English and Urdu newspapers(Daily Dawn, Express Tribune, Daily Jang and TheDuniya) ontheissueofKashmir which is the primary issue and bone of contention between the two nuclear states, Pakistan and India during the period of study (18th Feb 2016 to 17th Feb 2021).This study also explored the relationship between Pakistan and India in context of the Kashmir dispute and the relationship between the foreign policy and media. Forthispurpose,fourmainstreamnewspapers–two each of English (Daily Dawn, Express Tribune) and Urdu language newspapers(Daily Jang and Daily Duniya) were selected and their editorialcontents were analyzed. Theoretical approaches of Agenda setting and Framing (Goffman, 1974) were employed for their content examination.To measure the direction of the contents of editorials of selected four newspapers the reliance is on themethod that Berleson (1952)called “total problem” or “totality of impression” means the editorials were categorized into favorable, unfavorable and neutral.Selected all the four English and Urdu newspapers which published during the period of study are the universe. Non-Random– convenientsamplingtechnique isemployed.editorial coverage on daily basis regarding the issue of Kashmir published in sample newspapers during the period of study is the unit of analysis.It was found that English Newspapers (Daily Dawn and Express tribune)published 383 while 453editorials were published in Urdu language newspapers (Daily Jang and The Duniya) onIndo-PakConflictwithspecialreferencetoKashmirthroughouttheperiodofstudy. The findings of the study revealed that All newspapers had similar framingpattern on the issues including the right of self-determination, human rights violations in Indian occupied Kashmir, cease fire violations, political victimization, and illegal legislation in Indian occupied Kashmir. English and Urdu both languages leading newspapers of Pakistan framed the issues in the contextswhichsuitstheir respective governments andthenation’snarrative. However, Urdu language newspapers comparativelygave larger space to the Kashmir conflictascomparedtoEnglishlanguagenewspapers.